The global carbon cycle and climate change : scaling ecological energetics from organism to biosphere - Reichle, David E. (Elsevier, 2023)
The Global Carbon Cycle and Climate Change: Scaling Ecological Energetics from Organism to the Biosphere, Second Edition examines the global carbon cycle and energy balance of the biosphere, following carbon and energy through increasingly complex levels of metabolism-from cells to ecosystems. Utilizing scientific explanations, analyses of ecosystem functions, extensive references, and cutting-edge examples of energy flow in ecosystems, this is an essential resource to aid in understanding the scientific basis of the role of ecological systems in climate change. Includes new chapters on dynamic properties of the global carbon cycle, climate models and projections, and managing carbon in the global biogeochemical cycle.